Implementasi Program Mentoring Al-Qur’an dalam Meningkatkan Kemampuan Membaca Al-Qur’an Sesuai Kaidah Tajwid di Kelas X SMA PGII 2 Bandung - Reihan, Kemal Nan; Ikin Asikin; Diden Rosenda (Jurnal Riset Pendidikan Agama Islam, 2025)
Abstract. The percentage of students unable to read the Qur'an consistently remains high at the start of each new academic year. SMA PGII 2 Bandung has a flagship program aimed at improving students' ability to read the Qur'an. This research aims to explore the implementation of planning, execution, evaluation, as well as the supporting and inhibiting factors of the Qur'an mentoring program in enhancing the ability of 10th-grade students at SMA PGII 2 Bandung to read the Qur'an according to tajwid principles. This study employs a qualitative approach with a descriptive method. Data analysis techniques include data reduction, triangulation, and drawing conclusions. The research method used to delve into the program's processes and outcomes involves data collection through interviews, observations, and document studies. The findings indicate that the Qur'an mentoring program at SMA PGII 2 Bandung has significantly improved the ability of 10th-grade students to read the Qur'an, particularly in applying tajwid rules. Since the 2021–2022 academic year, the program has shown a substantial increase in the number of students with enhanced Qur'an reading skills. The program's success continues to develop through effective management. The implementation of the Qur'an mentoring program in the 2024–2025 academic year demonstrates the application of a structured implementation concept, including clear program policies, defined target groups, improvement goals, and responsible supervisors for program monitoring. This program has successfully supported the school's objective of producing a Qur'anic generation. However, some challenges remain, such as limited execution time, an insufficient number of mentors, and inadequate communication between the school and parents. These factors require evaluation to ensure the program's consistency and growth. Overall, the Qur'an mentoring program significantly benefits the development of students with noble character and proficiency in reading the Qur'an according to tajwid principles. Abstrak. Jumlah peserta didik tidak bisa membaca Al-Qur’an selalu tinggi persentasenya di setiap tahun ajaran baru. SMA PGII 2 Bandung memiliki program yang unggulan dalam peningkatan kemampuan membaca Al-Qur’an bagi peserta didik. Penelitian ini bertujuan untuk mengetahui implementasi perencanaan, pelaksanaan, evaluasi, serta faktor pendukung dan penghambat mentoring Al-Qur’an dalam meningkatkan kemampuan membaca Al-Qur’an sesuai kaidah tajwid siswa kelas X di SMA PGII 2 Bandung. Penelitian ini menggunakan pendekatan kualitatif dengan metode deskriptif. Teknik analisis data menggunakan reduksi data, triangulasi dan penarikan kesimpulan. Metode penelitian yang digunakan untuk mendalami proses dan hasil program adalah pengumpulan data melalui wawancara, observasi dan studi dokumentasi. Hasil penelitian menunjukkan bahwa program mentoring Al-Qur’an di SMA PGII 2 Bandung berhasil meningkatkan kemampuan membaca Al-Qur’an siswa kelas X secara signifikan, terutama dalam penerapan kaidah tajwid. Sejak tahun ajaran 2021-2022, program ini menghasilkan peningkatan jumlah siswa yang meningkat kualitas membaca Al-Qur’an. Keberhasilan program terus berkembang meliputi manajemen program yang baik. Pelaksanaan mentoring Al-Qur’an pada tahun ajaran 2024-2025 menunjukkan penerapan konsep implementasi yang terstruktur, meliputi adanya kebijakan program, kelompok sasaran yang jelas, target peningkatan, serta pelaksana yang bertanggung jawab dalam pengawasan program. Program ini berhasil dalam mendukung tujuan sekolah untuk mencetak generasi Qurani. Terkecuali, beberapa kekurangan masih menjadi tantangan, seperti keterbatasan waktu pelaksanaan, jumlah pementor yang kurang memadai, serta komunikasi antara sekolah dan orang tua siswa. Faktor-faktor ini perlu menjadi evaluasi agar program dapat terus konsisten dan berkembang. Secara keseluruhan, program mentoring Al-Qur’an memberikan manfaat signifikan dalam mencetak peserta didik yang berakhlakul karimah dan mahir membaca Al-Qur’an sesuai kaidah tajwid